Aedes aegypti lines for combined sterile insect technique and incompatible insect technique applications: the importance of host genomic background. Issue 6 (26th March 2020) - Carvalho, Danilo O.; Torres‐Monzon, Jorge A.; Koskinioti, Panagiota; Dilrukshi Wijegunawardana, N.D. Asha; Liang, Xiao; Pillwax, Gulizar; Xi, Zhiyong; Bourtzis, Kostas
Abstract: Aedes aegypti L. (Diptera: Culicidae), being the primary vector of pathogenic arboviruses, is a target for the development of novel genetic approaches to complement current conventional vector control strategies such as the combined sterile insect and incompatible insect technique (SIT/IIT). A transinfected line of Ae. aegypti carrying the w AlbB Wolbachia strain (WB2) was introgressed into two genomic backgrounds, Brazil and Mexico, producing two new Ae. aegypti strains (WB2‐BRA and WB2‐MEX). These strains were evaluated with respect to several life‐history traits such as fecundity, fertility, longevity, pupa size, pupation curve, and male mating competitiveness, as well as their response to irradiation. Our results show that the impact of Wolbachia infection depends on the genomic background and that the Brazilian one had no significant effect, whereas the Mexican one negatively affected fertility, longevity, and pupal size. Interestingly, Wolbachia ‐infected Ae. aegypti lines required a lower irradiation dose to achieve complete female sterility than the uninfected ones. The present findings are discussed given the potential use of Wolbachia ‐infected Ae. aegypti lines in combined SIT/IIT population suppression programs. Abstract : Aedes aegypti (Diptera: Culicidae), being the primary vector of pathogenic arboviruses, is a target for the development of novel genetic approaches to complement current conventional vector control strategies. In this manuscript, we present life‐history data and irradiation effects which support the potential use of Wolbachia ‐infected Ae. aegypti lines in combined sterile insect and incompatible insect technique (SIT/IIT) population suppression programs.